CHEMICAL CHARACTERIZATION OF PARTICULATE MATTER AT AN URBAN SITE OF HUANCAYO CITY, PERU - Suárez-Salas, Luis (2017)
Huancayo city, located at the Central Andes of Peru, presents air quality problems being the main pollutant the particulate matter (PM). For that reason, the objective of this paper was to characterize the chemical composition of atmospheric PM sampled in a station located in urban center of Huancayo city. It was sampled PM in august 2007, and January, April and May 2008 with a low volume sampler (Partisol FRM2000) and 47 mm filters. It was determined the concentration of particles smaller than 10 um, particles smaller than 2.5 um and it was analyzed the chemical composition up to 38 elements, using the X Rays Fluorescence (XRF) technique. In the case of (MP2,5) additional analysis were performed for ionic composition: nitrates (NO3 -), sulfates (SO4 = ) and carbonaceous species: organic carbon (COrg) and elemental carbon (CE). The results of MP10 (64.54 ±30.87 µg/m3 ) y MP2,5 (34.47 ±14.75 µg/m3 ) were higher that the annual Peruvian air quality standard, being the MP2,5 the one that registered higher values than other important cities. Also higher values of MP10 y MP2,5 were registered during the dry season. The determination of the chemical composition showed that geological elements (8%), metals (12%) and metalloids (7%) were the most abundant elements in the MP10 and the non-metals (4%), ions (11%) and carbonaceous species (44%) in the MP2,5. In conclusion this study confirms the problem of PM in Huancayo city, but provides important evidence the higher risk of MP2,5 to the health of its population, being the transport sector on of the most important emission sources.